Mozambique’s LNG revolution – A political risk outlook for the Rovuma LNG ventures - Fruehauf, A (Oxford Institute for Energy Studies, 2014)
The discovery of large natural gas fields in the Rovuma basin offshore East Africa represents one of the most exciting upstream exploration successes of recent years. The period of stability after the cessation of the civil war in 1992 allowed the international upstream companies to successfully apply advanced seismic and deep water drilling technology to identify a string of significant discoveries. In a very short time Mozambique found itself the owner of a world-class natural gas resource base. Mozambique is a ‘real time study’ of how a country of modest financial means succeeds (or fails) in its quest to successfully assimilate unexpected resource wealth. In this paper Anne Frühauf provides an extremely well structured analysis of these complexities as well as a masterful in-depth description and assessment of the political dynamics of Mozambique, which the Rovuma discoveries have re-invigorated, and which ultimately may be the most important factor determining the country’s fortunes.